FAKTOR YANG MEMPENGARUHI PERKEMBANGAN KARIR PESERTA DIDIK KELAS XII DI SMK NEGERI 1 PAINAN - Liliawati. D, Syefni - (Bimbingan dan Konseling, 2014)
This research is supported by factors that influenced the development of a career, that the students could not plan yet their future as well as determine career and life harmounious or appropriate, who could not understand and assess theirselves do not know yet various type of work that deals with the potential that exists in themselves, they still confused in the choices of career after graduated. The purpose of this research described: 1) The internal factors that influence the career development of students.2) The external factors that influence the career development of students. This research is descriptive quantitative research. Its population is all participants of class XII for 320 students. The sample was taken by using random sampling technique. This research took 76 students as main samples of this research. An instrument that used in this research is questionnaire. While for analysis of data in this research are used technique of percentage. The results of this research revealed that: The Internal factors that influence the career development of students in the category of many, and the external factors that influence the career development of students in the category of many, from the results of this research respondents recommend to the students in order to determine the factors that influence career development and develop their potential, BK teachers in order to provide effective career guidance services.